A method for producing a polymer-derived ceramic reinforced nickel-based composite
Patent Information
- Application Number
- CN202611069331.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]本发明的主要目的是为了解决现有技术中传统的陶瓷颗粒增强金属基复合材料中的陶瓷颗粒的添加方式导致的陶瓷颗粒在烧结产品中分布不均匀、容易团聚、无法实现综合力学性能和抗蠕变性能的协同提高等技术问题
[0028]上述方案,本发明提出了一种聚合物衍生陶瓷增强镍基复合材料的制备方法,能够解决现有技术中传统的陶瓷颗粒增强金属基复合材料中的陶瓷颗粒的添加方式导致的陶瓷颗粒在烧结产品中分布不均匀、容易团聚、无法实现综合力学性能和抗蠕变性能的协同提高等技术问题。
Smart Images

Figure CN122979686A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of ceramic-metal composite material preparation, and in particular to a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material. Background Technology
[0002] Ceramic particle-reinforced metal matrix composites not only possess excellent mechanical properties such as high strength, high toughness, good high-temperature creep resistance, and fatigue strength, but also have broad application prospects in aerospace, automotive, machinery, electronics, and nuclear industries. This composite material, by uniformly dispersing high-hardness, high-melting-point ceramic particles within a metal matrix, enables the metal material to achieve performance advantages that are difficult for traditional metal materials to match, such as "synergistic improvement in strength and toughness." Its unique performance advantages are mainly reflected in the fact that, while maintaining the good plasticity of the metal matrix, the introduction of the ceramic phase significantly improves the hardness and mechanical properties of the composite material. This performance optimization makes nickel-based composites suitable for critical components operating under harsh high-temperature conditions, such as in aerospace engines and gas turbines, and can also be applied to components in industries such as energy and rail transportation.
[0003] However, in traditional ceramic particle-reinforced metal matrix composites, the ceramic particles are usually added externally. The size and morphology of these ceramic particles depend on the initial state of the ceramic powder. Furthermore, smaller ceramic particles have a larger specific surface area, making them more prone to spontaneous aggregation. These aggregated particles are difficult to break down into individual particles within the nickel matrix, hindering the uniform dispersion of nanoparticles. In addition, the difference in melting points between metals and ceramics causes the ceramic phase to easily aggregate and distribute unevenly within the nickel matrix, resulting in significant defects in the composite material and hindering the achievement of good overall mechanical properties and creep resistance.
[0004] For example, Chinese patent CN117810392A discloses a polymer-derived ceramic composite material and its preparation method. The preparation method includes: adding a catalyst or initiator, a siloxane or polysiloxane containing Si-H bonds, a carbon-rich monomer or siloxane monomer containing multiple C=C double bonds, and a compound containing a transition metal element as a solute to a solvent and mixing them evenly; heating the resulting mixture to react and obtaining a precursor with a cross-linked structure; continuing to heat the precursor to remove the solvent and further solidify the precursor; and pyrolyzing the solidified product. Obviously, this method has technical defects such as a complex precursor preparation process and difficulty in further dispersing the precursor in a metal matrix after high-temperature pyrolysis.
[0005] Chinese patent CN117602943A discloses a method for preparing a ceramic matrix composite material with high sintering degree, comprising: providing a porous carbon / carbon composite material; uniformly mixing an oxygen-free tantalum carbide ceramic precursor with a polytitanium oxane to obtain a tantalum-titanium ceramic precursor; reacting the tantalum-titanium ceramic precursor with the porous carbon / carbon composite material by an impregnation pyrolysis method to obtain a ceramic matrix composite material. Obviously, this method has technical defects such as a cumbersome impregnation pyrolysis process, low density of the obtained composite material, and the technical route is not applicable to metal matrix composite materials.
[0006] Chinese patent CN115652121A discloses a ceramic particle-reinforced metal-based thermoelectric material and its preparation method, wherein the material consists of a matrix phase FeCoNi and a second phase Ta. b O2 constitutes the second phase Ta b O2 is dispersed in the matrix phase FeCoNi; the preparation method involves mixing raw material powders, high-energy ball milling, and sintering; obviously, a second phase Ta is present in this method. b O2 has technical drawbacks such as easy agglomeration and segregation of matrix elements during ball milling.
[0007] Chinese patent CN111270103A discloses a TiC particle-reinforced Ni composite porous material and its preparation process. The composite porous material is composed of Ni and TiC and has an open pore structure. The mass content of the TiC reinforcing phase is 5-45%. The preparation method is to prepare the raw material powder into a slurry, then impregnate an organic sponge template in the slurry, coat it with the slurry, dry it, and finally sinter it. Obviously, this method has technical defects such as low density of the resulting composite material, which leads to poor mechanical properties.
[0008] Therefore, there is an urgent need to develop a polymer-derived ceramic-reinforced nickel-based composite material to ensure that the ceramic phase is uniformly distributed in the nickel matrix without agglomeration, thereby synergistically improving the overall mechanical properties. Summary of the Invention
[0009] The main objective of this invention is to address the technical problems inherent in traditional ceramic particle-reinforced metal matrix composites, such as uneven distribution of ceramic particles in the sintered product, easy agglomeration, and the inability to achieve a synergistic improvement in comprehensive mechanical properties and creep resistance. Therefore, a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material is proposed, capable of solving the aforementioned problems.
[0010] The technical solution is as follows:
[0011] A method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, the method comprising the following steps:
[0012] S1. Thermal crosslinking: The liquid ceramic precursor is thermally crosslinked to obtain a bulk ceramic precursor.
[0013] S2. Grinding: Grind and crush the ceramic precursor block of S1 to obtain uniform ceramic precursor powder.
[0014] S3. Mixed ball milling: The uniform ceramic precursor powder from S2 is mixed and ball milled with nickel powder to obtain ceramic precursor / nickel composite powder.
[0015] S4. Thermal consolidation: The ceramic precursor / nickel composite powder of S3 is thermally consolidated to obtain a nickel-based composite material reinforced with nano-ceramic particles.
[0016] Optionally, the liquid ceramic precursor in S1 includes one or more of polymer-derived ceramics of polysilazane, polyboronsilazane, polycarbosilane, and polysiloxane, and polymer-derived ceramics modified thereon.
[0017] Optionally, the specific steps of thermal crosslinking in S1 are as follows: under a protective atmosphere, keep at 300-600℃ for 4-8 hours, with a heating and cooling rate of less than 2℃ / min.
[0018] Optionally, the grinding and crushing method in S2 is one or more of manual grinding, mechanical ball milling, and machine crushing.
[0019] Optionally, the average particle size of the ceramic precursor powder in S2 is 0.5-300 μm.
[0020] Optionally, the nickel powder in S3 is pure nickel powder or nickel alloy powder, and the mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder is 0.5-30%, with an average particle size of 1.0-50μm.
[0021] Optionally, the mixing and ball milling in S3 is carried out under vacuum conditions, with a vacuum degree of less than 0.1 Pa, a ball milling time of 5-40 h, a ball-to-material ratio of 10 / 1-20 / 1, a rotation speed of 200-500 rpm, and the particle size of the nickel powder is determined as needed.
[0022] Optionally, thermal consolidation in S4 includes: pressureless sintering, spark plasma sintering, hot pressing sintering, or hot isostatic pressing sintering.
[0023] Optionally, in S4, the heating rate of spark plasma sintering is 50-200℃ / min, the sintering temperature is 900-1100℃, the sintering time is 5-40min, and the pressure is not less than 30MPa; in S4, the heating rate of pressureless sintering, hot pressing sintering, and hot isostatic pressing sintering is 3-10℃ / min, the sintering temperature is 900-1300℃, the sintering time is 5-60min, and the pressure is 0-50MPa.
[0024] Optionally, in S4, the ceramic particle size of the nano-ceramic particle-reinforced nickel-based composite material is 200-800 nm, the nickel grain size is 0.5-3 μm, and the hardness of the composite material is 70-200 HV. 0.1 The composite material has a tensile strength of 200-700 MPa, a yield strength of 150-400 MPa, a yield-to-tensile ratio of 0.2-0.8, and an elongation after fracture of 0.5-30%.
[0025] Technical principle of the invention:
[0026] This invention utilizes the high-temperature pyrolysis characteristics of polymer-derived ceramics to achieve the dispersed distribution of nano-ceramic particles in nickel-based alloys, thereby improving the overall mechanical properties of nickel-based alloys. Specifically, the role of S1 thermal crosslinking is to crosslink and solidify the polymer-derived ceramic polysilazane, macroscopically changing it from a liquid to a solid for easy crushing, and microscopically forming a silicon-nitrogen network structure through polysilazane crosslinking, thus improving the ceramic yield; the role of S2 grinding and crushing is to crush the polysilazane solid obtained in S1 into polysilazane powder, which facilitates mixing and uniform dispersion with nickel powder; the role of S3 mixing and ball milling is to fully mix and further crush the polysilazane powder obtained in S2 with metallic nickel powder, which is beneficial for refining the polysilazane powder and dispersing it uniformly; the purpose of S4 thermal consolidation is to solidify the composite powder obtained in S3 into a dense composite material. The polysilazane generates nano-ceramic particles in situ at high temperature and disperses them uniformly in the nickel-based alloy. Continuous uniaxial pressure achieves high density and good overall mechanical properties of the composite material.
[0027] The above technical solution has at least the following advantages compared with the existing technology:
[0028] The present invention proposes a method for preparing polymer-derived ceramic-reinforced nickel-based composite materials, which can solve the technical problems in the existing technology, such as uneven distribution of ceramic particles in sintered products, easy agglomeration, and inability to achieve synergistic improvement of comprehensive mechanical properties and creep resistance, caused by the addition of ceramic particles in traditional ceramic particle-reinforced metal matrix composite materials.
[0029] The present invention provides a novel preparation route for polymer-derived ceramic-reinforced nickel-based composite materials. The method involves thermally crosslinking a liquid polysilazane precursor and crushing it into powder, which facilitates ball milling and mixing with metallic nickel powder. Finally, the uniformly mixed composite powder is solidified by spark plasma sintering.
[0030] The liquid ceramic precursor provided by the method of the present invention generates nano-ceramic particles in situ in a nickel matrix. The nano-ceramic particles are uniformly distributed in the nickel matrix, without obvious agglomeration, and have good interfacial bonding with the nickel matrix, without defects such as pores or cracks.
[0031] The method of this invention prepares polysilazane / nickel-based composite materials with excellent comprehensive mechanical properties through thermal crosslinking and crushing of polysilazane precursors and powder metallurgy. The composite materials have high density (>99.0%), good interfacial bonding between the in-situ generated polysilazane nano-ceramic particles and the nickel matrix, and excellent comprehensive mechanical properties.
[0032] The method for preparing polysilazane-reinforced nickel-based composite materials provided by the present invention has a short process, simple technology, and is suitable for large-scale production.
[0033] In summary, compared with existing technologies for ceramic particle-reinforced metal matrix composites, the method of this invention obtains nano-ceramic particle-reinforced nickel matrix composites through thermal crosslinking, grinding and crushing, mixed ball milling and thermal consolidation. This method is stable, easy to implement, low in cost and high in efficiency, and conducive to large-scale industrial production and application. Attached Figure Description
[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0035] Figure 1 This is a flowchart illustrating the preparation method of a polymer-derived ceramic-reinforced nickel-based composite material according to the present invention.
[0036] Figure 2 This is a scanning electron microscope image of a polysilazane / nickel composite material prepared by a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material according to Example 3 of the present invention;
[0037] Figure 3 This is a transmission electron microscope image of a polysilazane / nickel composite material prepared by a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material according to Example 3 of the present invention.
[0038] Figure 4 This is a graph showing the hardness test results of a polysilazane / nickel composite material prepared by a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material according to Example 3 of the present invention.
[0039] Figure 5 This is a stress-strain curve of a polysilazane / nickel composite material prepared by a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material according to Example 3 of the present invention. Detailed Implementation
[0040] The technical solution of the present invention will now be described with reference to the accompanying drawings.
[0041] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.
[0042] In the embodiments of the present invention, the terms "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction is not emphasized, their intended meanings are consistent.
[0043] In this embodiment of the invention, sometimes a subscript such as W1 may be written in a non-subscript form such as W1. When the difference is not emphasized, the meaning they express is the same.
[0044] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0045] A method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the method combines... Figure 1 Includes the following steps:
[0046] S1. Thermal crosslinking: The liquid ceramic precursor is thermally crosslinked to obtain a bulk ceramic precursor.
[0047] S2. Grinding: Grind and crush the ceramic precursor block of S1 to obtain uniform ceramic precursor powder.
[0048] S3. Mixed ball milling: The uniform ceramic precursor powder from S2 is mixed and ball milled with nickel powder to obtain ceramic precursor / nickel composite powder.
[0049] S4. Thermal consolidation: The ceramic precursor / nickel composite powder of S3 is thermally consolidated to obtain a nickel-based composite material reinforced with nano-ceramic particles.
[0050] Specifically, the liquid ceramic precursor in S1 includes one or more of polymer-derived ceramics of polysilazane, polyboronsilazane, polycarbosilane, and polysiloxane, and polymer-derived ceramics modified thereon.
[0051] Specifically, the thermal crosslinking steps in S1 are as follows: under a protective atmosphere, maintain the temperature at 300-600℃ for 4-8 hours, with a heating and cooling rate of less than 2℃ / min.
[0052] Specifically, the grinding and crushing method in S2 is one or more of manual grinding, mechanical ball milling, and machine crushing.
[0053] Specifically, the average particle size of the ceramic precursor powder in S2 is 0.5-300 μm.
[0054] Specifically, the nickel powder in S3 is pure nickel powder or nickel alloy powder, and the ceramic precursor in the ceramic precursor / nickel composite powder has a mass ratio of 0.5-30% and an average particle size of 1.0-50μm.
[0055] Specifically, the mixing and ball milling in S3 is carried out under vacuum conditions, with a vacuum degree of less than 0.1 Pa, a ball milling time of 5-40 h, a ball-to-material ratio of 10 / 1-20 / 1, a rotation speed of 200-500 rpm, and the particle size of the nickel powder is determined as needed.
[0056] Specifically, thermal consolidation in S4 includes: pressureless sintering, spark plasma sintering, hot pressing sintering, or hot isostatic pressing sintering.
[0057] Specifically, in S4, the heating rate of spark plasma sintering is 50-200℃ / min, the sintering temperature is 900-1100℃, the sintering time is 5-40min, and the pressure is not less than 30MPa; in S4, the heating rate of pressureless sintering, hot pressing sintering, and hot isostatic pressing sintering is 3-10℃ / min, the sintering temperature is 900-1300℃, the sintering time is 5-60min, and the pressure is 0-50MPa.
[0058] Specifically, in S4, the ceramic particle size of the nano-ceramic particle-reinforced nickel-based composite material is 200-800 nm, the nickel grain size is 0.5-3 μm, and the hardness of the composite material is 70-200 HV. 0.1 The composite material has a tensile strength of 200-700 MPa, a yield strength of 150-400 MPa, a yield-to-tensile ratio of 0.2-0.8, and an elongation after fracture of 0.5-30%.
[0059] Methods for testing the prepared polymer-derived ceramic-reinforced nickel-based composites include:
[0060] The microstructure of the polysilazane / nickel composite material prepared in the following examples was observed by scanning electron microscopy and transmission electron microscopy.
[0061] The hardness of polysilazane / nickel composite material was measured using a micro Vickers hardness tester as follows: the load was 100g, the holding time was 15s, the indentation was complete and clear without cracking, and the hardness result was calculated by measuring the diagonal length of the indentation.
[0062] The room temperature tensile strength of polysilazane / nickel composite material was determined using a universal mechanical testing machine as follows: dumbbell-shaped tensile specimens were cut from the polysilazane / nickel composite material by wire cutting with a gauge length of 15 mm and a tensile speed of 1 mm / min. To ensure the reliability of the data, three samples were tested for each component, and the average value was taken.
[0063] Example 1
[0064] This embodiment describes a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material is combined with... Figure 1 Includes the following steps:
[0065] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for at least 6 hours under an argon protective atmosphere. The heating and cooling rate is less than 2°C / min. After the tube furnace cools to room temperature, take out the thermally crosslinked product from the crucible to obtain the polysilazane block.
[0066] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0067] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass percentage of the ceramic precursor in the ceramic precursor / nickel composite powder was 0.5%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0068] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 is thermally solidified. 50g of the polysilazane / nickel composite powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0069] The ceramic particles in the nano-ceramic particle-reinforced nickel-based composite material have a particle size of 777 nm, the nickel grain size is 2.6 μm, and the hardness of the composite material is 173 HV. 0.1The composite material has a tensile strength of 532 MPa, a yield strength of 339 MPa, a yield-to-tensile ratio of 0.64, and an elongation after fracture of 10.6%.
[0070] Example 2
[0071] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0072] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for at least 6 hours under an argon protective atmosphere. The heating and cooling rate is less than 2°C / min. After the tube furnace cools to room temperature, take out the thermally crosslinked product from the crucible to obtain the polysilazane block.
[0073] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0074] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass percentage of the ceramic precursor in the ceramic precursor / nickel composite powder was 1.0%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0075] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 is thermally solidified. 50g of the polysilazane / nickel composite powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0076] The ceramic particles in the nano-ceramic particle-reinforced nickel-based composite material have a particle size of 446 nm, the nickel grain size is 2.7 μm, and the hardness of the composite material is 155 HV. 0.1 The composite material has a tensile strength of 590 MPa, a yield strength of 286 MPa, a yield-to-tensile ratio of 0.48, and an elongation after fracture of 23.1%.
[0077] Example 3
[0078] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0079] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for at least 6 hours under an argon protective atmosphere. The heating and cooling rate is less than 2°C / min. After the tube furnace cools to room temperature, take out the thermally crosslinked product from the crucible to obtain the polysilazane block.
[0080] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0081] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder was 1.5%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0082] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 is thermally solidified. 50g of the polysilazane / nickel composite powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0083] like Figure 2 and Figure 3 As shown, the nanoparticles generated by in-situ pyrolysis of polysilazane have a good interface with the nickel matrix, and there are no defects such as pores or microcracks at the interface.
[0084] The ceramic particles in the nano-ceramic particle-reinforced nickel-based composite material have a particle size of 223 nm, the nickel grain size is 2.4 μm, and the hardness of the composite material is 188 HV. 0.1 The composite material has a tensile strength of 642 MPa, a yield strength of 358 MPa, a yield-to-tensile ratio of 0.56, and an elongation after fracture of 18.1%.
[0085] Example 4
[0086] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0087] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for at least 6 hours under an argon protective atmosphere. The heating and cooling rate is less than 2°C / min. After the tube furnace cools to room temperature, take out the thermally crosslinked product from the crucible to obtain the polysilazane block.
[0088] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0089] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder was 2.5%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0090] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 is thermally solidified. 50g of the polysilazane / nickel composite powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0091] The ceramic particles in the nano-ceramic particle-reinforced nickel-based composite material have a particle size of 500 nm, the nickel grain size is 1.0 μm, and the hardness of the composite material is 169 HV. 0.1 The composite material has a tensile strength of 625 MPa, a yield strength of 380 MPa, a yield-to-tensile ratio of 0.61, and an elongation after fracture of 7.7%.
[0092] Comparative Example 1
[0093] Pure nickel samples were obtained by thermally solidifying raw material nickel powder through spark plasma sintering under the same sintering process as in Example 1.
[0094] The hardness of the pure nickel sample is 126 HV. 0.1 The pure nickel grain size is 48.0 μm, the tensile strength is 435 MPa, the yield strength is 174 MPa, the yield ratio is 0.4, and the elongation after fracture is 42.3%.
[0095] Figure 4 The results show the hardness test results for Examples 1-4 and Comparative Example 1. Figure 4 It can be seen that the hardness of the polysilazane / nickel composite material is higher than that of pure nickel. With the increase of polysilazane content, the hardness of the polysilazane / nickel composite material first increases and then decreases, reaching its highest value of 188 HV when the polysilazane content is 1.5%. 0.1 This indicates that polysilazane has a good reinforcing effect.
[0096] Figure 5 The tensile strength test results are for Examples 1-4 and Comparative Example 1. From... Figure 5 It can be seen that the tensile strength of the polysilazane / nickel composite material is higher than that of pure nickel. With the increase of polysilazane content, the tensile strength of the polysilazane / nickel composite material first increases and then decreases. When the polysilazane content is 1.5%, the composite material achieves good synergy between strength and plasticity, indicating that polysilazane has a good strengthening effect.
[0097] Example 5
[0098] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polycarbosilane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0099] S1. Grinding: Place nickel powder in an agate mortar, add polycarbosilane precursor and grind thoroughly to obtain polycarbosilane / nickel mixed powder; wherein, the selected raw material nickel powder has a purity of 99.95%, a nominal particle size of 1-3μm, and a powder morphology of nearly spherical.
[0100] S2. Mixed ball milling: The polycarbosilane / nickel mixed powder of S1 is mixed and ball milled. The mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder is 0.5%. The process is carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa. The ball milling time is 10 h, the ball-to-material ratio is 14 / 1, and the rotation speed is 500 rpm. After ball milling, the mixed powder is taken out to obtain polycarbosilane / nickel composite powder.
[0101] S3. Thermal Consolidation: The polycarbosilane / nickel composite powder of S2 is thermally solidified. 50g of the powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0102] The ceramic particles in the nano-ceramic particle-reinforced nickel-based composite material have a particle size of 466 nm, the nickel grain size in the composite material is 2.5 μm, and the hardness of the composite material is 182 HV. 0.1 The composite material has a tensile strength of 697 MPa, a yield strength of 359 MPa, a yield-to-tensile ratio of 0.52, and an elongation after fracture of 27.8%.
[0103] Example 6
[0104] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0105] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for 6 hours under an argon protective atmosphere with a heating and cooling rate of 1°C / min. After the tube furnace cools to room temperature, take out the thermally crosslinked product from the crucible to obtain the polysilazane block.
[0106] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0107] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder was 2.5%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0108] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 was thermally consolidated. 35g of the powder was placed on a press and cold-pressed into a green compact, followed by pressureless sintering. The forming pressure was 60MPa, and the pressureless sintering was carried out under an argon protective atmosphere at a sintering temperature of 1200℃ for 60min at a heating rate of 3℃ / min. After sintering, the furnace was allowed to cool to room temperature, resulting in a compact with dimensions of [dimensions to be filled in]. 25mm×8mm nano-ceramic particle reinforced nickel-based composite material.
[0109] The hardness of the nano-ceramic particle-reinforced nickel-based composite material is 75 HV. 0.1 The composite material has a tensile strength of 211 MPa, a yield strength of 187 MPa, a yield-to-tensile ratio of 0.89, and an elongation after fracture of 0.4%.
[0110] Example 7
[0111] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polysilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0112] S1. Thermal crosslinking: Place the alumina crucible containing the liquid polysilazane precursor in a tube furnace and keep it at 375°C for 6 hours under an argon protective atmosphere. The heating and cooling rate is less than 1°C / min. After the tube furnace cools to room temperature, take out the thermal crosslinked product from the crucible to obtain the polysilazane block.
[0113] S2, Grinding: Place the polysilazane block from S1 in an agate mortar and grind it thoroughly to obtain a uniform and fine polysilazane powder with an average particle size of 112μm.
[0114] S3. Mixed ball milling: The uniform and fine polysilazane powder from S2 was mixed and ball milled with nickel powder. The mass ratio of ceramic precursor in the ceramic precursor / nickel composite powder was 1.5%. The process was carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa, a ball milling time of 10 h, a ball-to-powder ratio of 14 / 1, and a rotation speed of 500 rpm. After ball milling, the mixed powder was taken out to obtain polysilazane / nickel composite powder. The selected raw material nickel powder had a purity of 99.95%, a nominal particle size of 1-3 μm, a near-spherical powder morphology, and good dispersion.
[0115] S4. Thermal Consolidation: The polysilazane / nickel composite powder of S3 is thermally solidified. 80g of polysilazane / nickel composite powder is placed in a graphite mold, compacted, and then hot-pressed and sintered under an argon atmosphere at a temperature of 1100℃, a pressure of 40MPa, a holding time of 30min, and a heating rate of 1℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 50mm×6mm nano-ceramic particle reinforced nickel-based composite material.
[0116] The hardness of the nano-ceramic particle-reinforced nickel-based composite material is 184 HV. 0.1 The composite material has a tensile strength of 474 MPa, a yield strength of 227 MPa, a yield-to-tensile ratio of 0.48, and an elongation after fracture of 25.3%.
[0117] Example 8
[0118] This embodiment discloses a method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, wherein the liquid ceramic precursor is selected as a liquid polyborosilazane precursor, and the method for preparing the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps:
[0119] S1. Grinding: Place nickel powder in an agate mortar, add polyborosilicate precursor and grind thoroughly to obtain polyborosilicate / nickel mixed powder; wherein, the selected raw material nickel powder has a purity of 99.95%, a nominal particle size of 1-3μm, and a powder morphology of nearly spherical.
[0120] S2. Mixed ball milling: The polyborosilicate / nickel mixed powder from S1 is mixed and ball milled. The mass percentage of the ceramic precursor in the ceramic precursor / nickel composite powder is 0.75%. The process is carried out under vacuum conditions with a vacuum degree of less than 0.1 Pa. The ball milling time is 10 h, the ball-to-material ratio is 14 / 1, and the rotation speed is 500 rpm. After ball milling, the mixed powder is taken out to obtain the polyborosilicate / nickel composite powder.
[0121] S3. Thermal Consolidation: The polyborosilicate / nickel composite powder of S2 is thermally solidified. 50g of the powder is placed in a graphite mold, compacted, and then subjected to spark plasma sintering under vacuum conditions (~5Pa). The sintering temperature is 1100℃, the pressure is 40MPa, the holding time is 10min, and the heating rate is 100℃ / min. After sintering, the furnace chamber is allowed to cool to room temperature. The mold is then removed, and the product is demolded to obtain dimensions of [dimensions missing]. 30mm×10mm nano-ceramic particle reinforced nickel-based composite material.
[0122] The hardness of the nano-ceramic particle-reinforced nickel-based composite material is 161 HV. 0.1 The composite material has a tensile strength of 558 MPa, a yield strength of 245 MPa, a yield-to-tensile ratio of 0.44, and an elongation after fracture of 26.0%.
[0123] The present invention proposes a method for preparing polymer-derived ceramic-reinforced nickel-based composite materials, which can solve the technical problems in the existing technology, such as uneven distribution of ceramic particles in sintered products, easy agglomeration, and inability to achieve synergistic improvement of comprehensive mechanical properties and creep resistance, caused by the addition of ceramic particles in traditional ceramic particle-reinforced metal matrix composite materials.
[0124] The present invention provides a novel preparation route for polymer-derived ceramic-reinforced nickel-based composite materials. The method involves thermally crosslinking a liquid polysilazane precursor and crushing it into powder, which facilitates ball milling and mixing with metallic nickel powder. Finally, the uniformly mixed composite powder is solidified by spark plasma sintering.
[0125] The liquid ceramic precursor provided by the method of the present invention generates nano-ceramic particles in situ in a nickel matrix. The nano-ceramic particles are uniformly distributed in the nickel matrix, without obvious agglomeration, and have good interfacial bonding with the nickel matrix, without defects such as pores or cracks.
[0126] The method of this invention prepares polysilazane / nickel-based composite materials with excellent comprehensive mechanical properties through thermal crosslinking and crushing of polysilazane precursors and powder metallurgy. The composite materials have high density (>99.0%), good interfacial bonding between the in-situ generated polysilazane nano-ceramic particles and the nickel matrix, and excellent comprehensive mechanical properties.
[0127] The method for preparing polysilazane-reinforced nickel-based composite materials provided by the present invention has a short process, simple technology, and is suitable for large-scale production.
[0128] In summary, compared with existing technologies for ceramic particle-reinforced metal matrix composites, the method of this invention obtains nano-ceramic particle-reinforced nickel matrix composites through thermal crosslinking, grinding and crushing, mixed ball milling and thermal consolidation. This method is stable, easy to implement, low in cost and high in efficiency, and conducive to large-scale industrial production and application.
[0129] It should be understood that the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. Additionally, the character " / " in this article generally indicates an "or" relationship between the preceding and following related objects, but it can also represent an "and / or" relationship. Please refer to the context for a more accurate understanding.
[0130] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, and c can be a single item or multiple items.
[0131] It should be understood that, in various embodiments of the present invention, the sequence number of each process does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0132] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing a polymer-derived ceramic-reinforced nickel-based composite material, characterized in that, The preparation method of the polymer-derived ceramic-reinforced nickel-based composite material includes the following steps: S1. Thermal crosslinking: The liquid ceramic precursor is thermally crosslinked to obtain a bulk ceramic precursor. S2. Grinding: Grind and crush the ceramic precursor block of S1 to obtain uniform ceramic precursor powder. S3. Mixed ball milling: The uniform ceramic precursor powder from S2 is mixed and ball milled with nickel powder to obtain ceramic precursor / nickel composite powder. S4. Thermal consolidation: The ceramic precursor / nickel composite powder of S3 is thermally consolidated to obtain a nickel-based composite material reinforced with nano-ceramic particles.
2. The method for preparing polymer-derived ceramic-reinforced nickel-based composite materials according to claim 1, characterized in that, The liquid ceramic precursor in S1 includes one or more of the following: polymer-derived ceramics of polysilazane, polyboronsilazane, polycarbosilane, and polysiloxane, and polymer-derived ceramics modified thereon.
3. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The specific steps for thermal crosslinking in S1 are as follows: under a protective atmosphere, keep warm at 300-600℃ for 4-8 hours, with a heating and cooling rate of less than 2℃ / min.
4. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The grinding and crushing methods in S2 are one or more of manual grinding, mechanical ball milling, and machine crushing.
5. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The average particle size of the ceramic precursor powder in S2 is 0.5-300 μm.
6. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The nickel powder in S3 is pure nickel powder or nickel alloy powder. The ceramic precursor in the ceramic precursor / nickel composite powder has a mass ratio of 0.5-30% and an average particle size of 1.0-50μm.
7. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The specific process of ball milling in S3 is as follows: it is carried out under vacuum conditions, with a vacuum degree of less than 0.1 Pa, a ball milling time of 5-40 h, a ball-to-material ratio of 10 / 1-20 / 1, a rotation speed of 200-500 rpm, and the particle size of the nickel powder is determined as needed.
8. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, Thermal consolidation in S4 includes: pressureless sintering, spark plasma sintering, hot pressing sintering, or hot isostatic pressing sintering.
9. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, In S4, the heating rate for spark plasma sintering is 50-200℃ / min, the sintering temperature is 900-1100℃, the sintering time is 5-40min, and the pressure is not less than 30MPa; in S4, the heating rate for pressureless sintering, hot pressing sintering, and hot isostatic pressing sintering is 3-10℃ / min, the sintering temperature is 900-1300℃, the sintering time is 5-60min, and the pressure is 0-50MPa.
10. The method for preparing the polymer-derived ceramic-reinforced nickel-based composite material according to claim 1, characterized in that, The ceramic particle size of the S4 nano-ceramic particle-reinforced nickel-based composite material is 200-800 nm, the nickel grain size is 0.5-3 μm, and the hardness of the composite material is 70-200 HV. 0.1 The composite material has a tensile strength of 200-700 MPa, a yield strength of 150-400 MPa, a yield-to-tensile ratio of 0.2-0.8, and an elongation after fracture of 0.5-30%.
Citation Information
Patent Citations
TiC particle reinforced Ni composite porous material and preparation process thereof
CN111270103A
Ceramic particle reinforced metal-based thermoelectric material and preparation method thereof
CN115652121A
High-sintering-degree ceramic-based composite material and preparation method thereof
CN117602943A
Ceramic composite material derived from polymer as well as preparation method and application of ceramic composite material
CN117810392A